Laboratory colonization of Aedes lineatopennis - Jitpakdi A. (2014)
Aedes lineatopennis, a species member of the subgenus Neomelaniconion, could be colonized for more than 10 successive generations from 30 egg batches [totally 2,075 (34-98) eggs] of wild-caught females. The oviposited eggs needed to be incubated in a moisture chamber for at least 7 days to complete embryonation and, following immersion in 0.25-2% hay-fermented water, 61-66% of them hatched after hatching stimulation. Larvae were easily reared in 0.25-1% hay-fermented water, with suspended powder of equal weight of wheat germ, dry yeast, and oatmeal provided as food. Larval development was complete after 4-6 days. The pupal stage lasted 3-4 days when nearly all pupae reached the adult stage (87-91%). The adults had to mate artificially, and 5-day-old males proved to be the best age for induced copulation. Three to five-day-old females, which were kept in a paper cup, were fed easily on blood from an anesthetized golden hamster that was placed on the top-screen. The average number of eggs per gravid female was 63.56 +/- 22.93 (22-110). Unfed females and males, which were kept in a paper cup and fed on 5% multivitamin syrup solution, lived up to 43.17 +/- 12.63 (9-69) and 15.90 +/- 7.24 (2-39) days, respectively, in insectarium conditions of 27 +/- 2 degrees C and 70-80% relative humidity.